Association of HIV, hepatitis C virus and liver fibrosis severity with interleukin-6 and C-reactive protein levels. (17th July 2015) - Shah, Shailja; Ma, Yifei; Scherzer, Rebecca; Huhn, Greg; French, Audrey L.; Plankey, Michael; Peters, Marion G.; Grunfeld, Carl; Tien, Phyllis C.
Abstract : Background: Hepatitis C virus (HCV) infection is associated with chronic inflammation; yet studies show greater interleukin (IL)-6, but lower C-reactive protein (CRP) levels. We determined whether liver fibrosis severity and HCV replication affect the ability of IL-6 to stimulate the production of CRP from the liver. Methods: We used multivariable generalized linear regression to examine the association of HIV, HCV and transient elastography-measured liver stiffness with IL-6 and CRP in participants (164 HIV-monoinfected; 10 HCV-monoinfected; 73 HIV/HCV-coinfected; 59 neither infection) of the Women's Interagency HIV Study. Significant fibrosis was defined as liver stiffness greater than 7.1 kPa. Results: IL-6 was positively correlated with CRP levels in all women, but CRP levels were lower in HCV-infected women (with and without HIV infection) at all levels of IL-6. HCV-infected women with fibrosis had nearly 2.7-fold higher IL-6 levels compared to controls [95% confidence interval (CI 146%, 447%]; HCV-infected women without fibrosis had IL-6 levels that were similar to controls. By contrast, CRP was 28% lower in HCV-infected women with fibrosis (95% CI −55%, 15%) and 47% lower in HCV-infected women without fibrosis (95% CI −68%, −12%). Among the HCV-infected women, higher HCV-RNA levels were associated with 9% lower CRP levels per doubling (95% CI −18%, 0%). Conclusion: Liver fibrosis severity is associated with greater IL-6 levels, but the stimulatory effect of IL-6 on CRP appears to be blunted by HCV replication rather than by liver fibrosis severity. Investigation of the potential CRP rebound after HCV-RNA eradication and persistent liver fibrosis on organ injury is needed.